Microbial biotechnology in agriculture and aquaculture - Ray, Ramesh C. (Science Publishers, 2005)
Annotation In agriculture, microbial biotechnology covers a wide array of subjects ranging from biofertilizers to biological control of pests and diseases; from biological N 2 -fixation to lignocellulose degradation; from production of biomass and biofuels to genetically engineered plants. Similarly, microbial biotechnology in aquaculture touches several aspects such as biofilms, bioprocessing of biomaterials (metabolites, enzymes, proteins, exopolysaccharides, etc.), application of biofertilizers, probiotics, bio-remediation of contaminated water, etc. This book is an attempt to highlight the significant aspects of the vast subject area like application of microbial biotechnology in agriculture and aquaculture.